Driving condition based mode switching optimal controller for improved driveability - Caba, Z.; Atabay, O.; Güney, A. (Elsevier BV, 2017)
Abstract Driveability is an important attribute of the road vehicles. Driveline oscillations caused by load changes in the driveline are deteriorating driveability of the vehicle and may cause discomfort by the driver. Load changes in the driveline may occur during tip-in and tip-out manoeuvres or during gear changes. Controllers that reduce driveline oscillations have to balance the trade-off between performance feel and comfort. Therefore, the controller needs to assess the driver expectation and needs to have a metric for the target vehicle response accordingly. An optimal controller structure is designed with different cost functions to be effective in different driving modes. To switch between modes, a mode selector state machine is designed. In order to ensure that the trade-off is done correctly, a tip-in detection algorithm is implemented. Desired response of the vehicle is ensured via an acceleration set point generator. The effectiveness of the controller is shown with simulation results.